Acaricide resistance patterns in one-host Rhipicephalus spp. at communal dip tanks and neighbouring commercial farms in the KwaZulu-Natal Midlands - Stoltsz, Wilhelm Heinrich (University of Pretoria, 2020)
Dissertation (MSc (Tropical Animal Health))--University of Pretoria, 2019.